Acrylamide formation and antioxidant activity in coffee during roasting – A systematic study. (1st May 2021) - Schouten, Maria Alessia; Tappi, Silvia; Angeloni, Simone; Cortese, Manuela; Caprioli, Giovanni; Vittori, Sauro; Romani, Santina
Highlights: The risks/benefits induced by roasting thermal process in coffee were evaluated. Acrylamide and antioxidant activity decreased during prolonged roasting process. Robusta samples showed the highest acrylamide and antioxidant compounds content. Antioxidant levels are related to degradation/formation of beneficial compounds. Abstract: The aim of this study was to investigate the effect of the coffee roasting process on both toxic and some beneficial antioxidant compounds, applying a systematic and broad approach. Arabica and Robusta green coffee beans were roasted in a lab-scale roaster for different times in order to achieve five roasting degrees (from light to dark) and to assess the evolution of acrylamide (AA), trigonelline, nicotinic acid and caffeoylquinic acids contents (determined by HPLC) as well as antioxidant activity (evaluated by Folin-Ciocalteu, FRAP, DPPH, ABTS assays). The results confirmed that the AA levels and antioxidant activity reached a maximum in the first coffee roasting degrees and then decreased prolonging the heating process, both in Arabica and Robusta samples. Nevertheless, the thermal reduction observed was greater for AA compared to antioxidant activity, which was only slightly reduced due to the balance between the degradation and the neoformation of antioxidant compounds.